2012
DOI: 10.1590/s1806-83242012000100012
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and interleukin-6 levels in insulin-treated diabetic rats with experimental periodontitis

Abstract: The aim of the study was to compare the serum levels of adiponectin and interleukin-6 (IL-6) in insulin-treated diabetic rats with or without periodontitis. Forty male Wistar rats were randomly divided into 2 groups (20 rats each): a) insulin-treated diabetic group (control, DI) and b) insulin-treated diabetic periodontitis group (test, DIP). Diabetes was induced, and insulin treatment was initiated on day 5. On day 16, periodontitis was induced in the DIP group. All rats were euthanized on day 77. Adiponectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…187 The mechanisms by which periodontitis affects diabetes are not entirely clear but include increased circulating levels of different cytokines, such as interleukin-1-beta, tumor necrosis factor-alpha, and adiponectin, as well as increased adipose tissue inflammation. 184,185,188 Taken together, animal studies also point to the bidirectional role of diabetes and periodontitis and shed some light on the mechanism by which these conditions lead to a pro-inflammatory response.…”
Section: Lessons From Animal Models: Interactions Between Diabetes and Periodontitismentioning
confidence: 96%
See 1 more Smart Citation
“…187 The mechanisms by which periodontitis affects diabetes are not entirely clear but include increased circulating levels of different cytokines, such as interleukin-1-beta, tumor necrosis factor-alpha, and adiponectin, as well as increased adipose tissue inflammation. 184,185,188 Taken together, animal studies also point to the bidirectional role of diabetes and periodontitis and shed some light on the mechanism by which these conditions lead to a pro-inflammatory response.…”
Section: Lessons From Animal Models: Interactions Between Diabetes and Periodontitismentioning
confidence: 96%
“…Periodontitis even alters glucose metabolism in rodents with prediabetes 187 . The mechanisms by which periodontitis affects diabetes are not entirely clear but include increased circulating levels of different cytokines, such as interleukin‐1‐beta, tumor necrosis factor‐alpha, and adiponectin, as well as increased adipose tissue inflammation 184,185,188 …”
Section: Diabetesmentioning
confidence: 99%
“…Adiponectin can reduce insulin resistance and enhance the action of insulin in the liver, resulting in a reduction of blood glucose levels . In a recent study, a statistically significant increase in levels of adiponectin was observed in diabetic rats with experimental periodontitis …”
Section: Diabetes As a Risk And Modifying Factor For Periodontitismentioning
confidence: 98%
“…41,42 In a recent study, a statistically significant increase in levels of adiponectin was observed in diabetic rats with experimental periodontitis. 43 Leptin is produced by the ob (obese) gene in adipose tissue cells, especially in white adipose tissue, its action is on the hypothalamus resulting in decreased food intake and increased energy consumption. 44,45 Leptin increases insulin sensitivity by influencing insulin secretion, glucose utilisation, glycogen synthesis and fatty acid metabolism.…”
Section: How Diabetes Affects Periodontal Health Adipokines and Inflamentioning
confidence: 99%
“…In addition, overexpression of AGEs/RAGE exacerbates the inflammatory response, thereby aggravating the destruction of periodontal tissue in patients with diabetes [ 20 ]. Periodontitis can aggravate the systemic inflammatory response through persistent bacteremia and elevate the levels of proinflammatory cytokines such as IL-6 and TNF- α [ 21 ], reduce the sensitivity of target cells to insulin, promote insulin resistance [ 22 ], and interfere with the normal metabolism of the body, thereby aggravating the metabolic disorder of diabetes. In brief, periodontitis combined with diabetes aggravates the pathology of these two diseases, so it is necessary to explore a drug that can treat these two diseases simultaneously.…”
Section: Discussionmentioning
confidence: 99%